2020
DOI: 10.3892/ijmm.2020.4536
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin attenuates sepsis‑induced myocardial�injury by enhancing autophagy in mice

Abstract: Sepsis-induced cardiomyopathy (SIc) is a complication of severe sepsis and septic shock characterized by an invertible myocardial depression. This study sought to explore the potential effects and mechanism of luteolin, a flavonoid polyphenolic compound, in lipopolysaccharide (LPS)-induced myocardial injury. Experimental mice were randomly allocated into 3 groups (25 mice in each group): The control group (Nc), the LPS group (LPS) and the LPS + luteolin group (LPS + Lut). Before the SIc model was induced, lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 55 publications
2
58
0
Order By: Relevance
“…Besides, after coincubation with BafA1, LC3Ⅱ and P62 levels were significantly improved, indicating that LPS treatment could trigger a low level of autophagy instead of impairment in autophagic flux ( Figure 2A ). Previous studies have suggested that activation of autophagy could contribute to suppressing LPS-induced cell toxicity ( Sun et al, 2018 ; Quach et al, 2019 ; Wu et al, 2020 ), autophagy influences the clearance of damaged proteins and organelles ( Yang and Klionsky, 2010 ). After pretreatment with Cap, LC3Ⅱ was significantly increased and P62 degradation was declined ( Figures 2B–E ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, after coincubation with BafA1, LC3Ⅱ and P62 levels were significantly improved, indicating that LPS treatment could trigger a low level of autophagy instead of impairment in autophagic flux ( Figure 2A ). Previous studies have suggested that activation of autophagy could contribute to suppressing LPS-induced cell toxicity ( Sun et al, 2018 ; Quach et al, 2019 ; Wu et al, 2020 ), autophagy influences the clearance of damaged proteins and organelles ( Yang and Klionsky, 2010 ). After pretreatment with Cap, LC3Ⅱ was significantly increased and P62 degradation was declined ( Figures 2B–E ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple antioxidant enzymes (eg SOD) are crucial to protect against mitochondrial oxidative stress. Mounting evidence has proved that sepsis‐induced myocardial injury could be attenuated by inhibiting oxidative stress and mitochondrial dysfunction 43,44 . A recent research showed that inhibition of PARP1 delayed the progression of Chagasic cardiomyopathy through improving mitochondria function and maintaining oxidant/antioxidant balance 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Impressively, intraperitoneal injection of luteolin in mice with lipopolysaccharide-induced myocardial injury mitigated mitochondrial injury and oxidative stress by decreasing AMPK phosphorylation in septic heart tissue and stabilizing the mitochondrial membrane potential. In summary, luteolin attenuates lipopolysaccharideinduced myocardial injury associated with mitochondrial impairments in mice through the inhibition of apoptosis and enhancing autophagy via modulation of AMPK signaling [16]. Furthermore, icariin, a prenylated flavonol glycoside, protected H9C2 cardiomyocytes from oxidative stress by scavenging ROS and promoting ERK pathway phosphorylation.…”
Section: Cardiovascular Diseasesmentioning
confidence: 95%
“…In recent years, the beneficial health effects of flavonoids, naturally occurring polyphenolic compounds, have attracted medical research, including their utilization in pathologies associated with mitochondrial impairments [11] such as cancers, cardiovascular and neurodegenerative diseases [12]. The efficacy of flavonoids is supported by extensive preclinical evidence that represents the basis for further research into the potential future use of these compounds in specific targeted and personalized therapy of mitochondriopathies according to the 3PM approach [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%